Oscar, are you sure you know why your examples are 'martingales'?
(proofs in first and second parts are just formalities)
Let $(\Omega, \mathscr F, \mathbb P)$ be our probability space.
Let $Y_0, Y_1, Y_2, ...$ be iid random variables s.t. $P(Y_i = 1) = 1/2 = P(Y_i = -1)$. Define $W^Y_n := \sum_{i=0}^{n} Y_i$.
Let $X_0, X_1, X_2, ...$ be iid random variables s.t. $P(X_i = 1) = 1/2 = P(X_i = -1)$. Define $W^X_n := \sum_{i=0}^{n} X_i$.
Firstly, note that $W^X_n$ and $W^Y_n$ martingales w/rt their natural filtrations (this corresponds to your definition of martingale) ie
$$E[W^X_n|W^X_0, W^X_1, ..., W^X_{n-1}] = E[W^X_n|\mathscr F_{n-1}^{W^X}] = W^X_{n-1}$$
$$E[W^Y_n|W^Y_0, W^Y_1, ..., W^Y_{n-1}] = E[W^Y_n|\mathscr F_{n-1}^{W^Y}] = W^Y_{n-1}$$
They are also martingales w/rt to the natural filtrations of X and Y, resp ie
$$E[W^X_n|X_0, X_1, ..., X_{n-1}] = E[W^X_n|\mathscr F_{n-1}^{X}] = W^X_{n-1}$$
$$E[W^Y_n|Y_0, Y_1, ..., Y_{n-1}] = E[W^Y_n|\mathscr F_{n-1}^{Y}] = W^Y_{n-1}$$
Actually, the latter equations are easier to prove than the former equations.
Proof of the former equations (I'll just use X):
$$\mathscr F_{n-1}^{X} \supseteq \mathscr F_{n-1}^{W^X} \tag{*}$$
Then we have
$$E[W^X_n|\mathscr F_{n-1}^{W^X}] = E[X_0 + X_1 + ... + X_{n-1} + X_n|\mathscr F_{n-1}^{W^X}]$$
$$ = E[X_0 + X_1 + ... + X_{n-1}|\mathscr F_{n-1}^{W^X}] + E[X_n|\mathscr F_{n-1}^{W^X}]$$
Consider the first term.
$$E[X_0 + X_1 + ... + X_{n-1}|\mathscr F_{n-1}^{W^X}] = \sum_{k=0}^{n-1} E[X_{i}|\mathscr F_{n-1}^{W^X}]$$
Consider the summand. Convince yourself that $X_i$ is $\mathscr F_{i}^{W^X}$-measurable (if we know $X_0, X_0 + X_1, ..., X_0 + X_1 + ... + X_i$, then we know $X_i$). Then $\because \mathscr F_{i}^{W^X} \subseteq \mathscr F_{n-1}^{W^X}$, we have that $X_i$ is $\mathscr F_{n-1}^{W^X}$-measurable. Hence,
$$E[X_{i}|\mathscr F_{n-1}^{W^X}] = X_i$$
Consider the second term $$E[X_n|\mathscr F_{n-1}^{W^X}]$$
By $(*)$ and the the tower property of conditional expectation, we have
$$E[X_n|\mathscr F_{n-1}^{W^X}] = E[E[X_n|\mathscr F_{n-1}^{W^X}]|\mathscr F_{n-1}^{X}]$$
Essentially, the tower property of conditional expectation states that the smaller filtration wins. Hence, it is also true that
$$E[X_n|\mathscr F_{n-1}^{W^X}] = E[E[X_n|\mathscr F_{n-1}^{X}]|\mathscr F_{n-1}^{W^X}]$$
Thus, we have
$$E[X_n|\mathscr F_{n-1}^{W^X}] = E[E[X_n|\mathscr F_{n-1}^{W^X}]|\mathscr F_{n-1}^{X}] = E[E[X_n|\mathscr F_{n-1}^{X}]|\mathscr F_{n-1}^{W^X}]$$
By independence, we have:
$$= E[E[X_n]|\mathscr F_{n-1}^{W^X}] = E[X_n] = 0$$
Hopefully, you're convinced that it's much easier to prove the latter than the former equations.
Secondly, consider
$$M_n = W_n^X 1_{A_n} + W_n^Y 1_{A_n^C}$$
where $A_n = \{W_n^X \ge W_n^Y\}$ and $0 < P(A_n) < 1$
Let us try to show (and hopefully fail in trying) that
$$E[M_n|\mathscr F_{n-1}^M] = M_{n-1}$$
where $\mathscr F_{n-1}^M = \sigma(M_0, M_1, ..., M_{n-1})$
Hopefully, you understand that it's possible to do the following:
$$E[M_n|\mathscr F_{n-1}^M] = E[E[M_n|\mathscr F_{n-1}]|\mathscr F_{n-1}^M]$$
where $\mathscr F_{n} := \sigma(\mathscr F_{n}^X, \mathscr F_{n}^Y) \supseteq \sigma(\mathscr F_{n}^{W^X}, \mathscr F_{n}^{W^Y}) \supseteq \mathscr F_n^M$
Thus, if $E[M_n|\mathscr F_{n-1}] = M_{n-1}$, then $E[M_n|\mathscr F_{n-1}^M] = M_{n-1}$. So hopefully, $E[M_n|\mathscr F_{n-1}] \ne M_{n-1}$.
Finally, let's compute
$$E[M_n|\mathscr F_{n-1}] = E[W_n^X 1_{A_n} + W_n^Y 1_{A_n^C}|\mathscr F_{n-1}] $$
$$= E[W_n^X 1_{A_n}|\mathscr F_{n-1}] + E[W_n^Y 1_{A_n^C}|\mathscr F_{n-1}] $$.
Now consider this. If at time 1, we have that $W_1^X = 2$ and $W_1^Y = 1$, it's possible that $W_2^X = 1$ and $W_2^Y = 2$. Thus, $M_2 = W_2^Y$ but $M_1 = W_1^X$
Formally:
If at time n, we have $\omega \in A_n$ (ie $W_n^X(\omega) \ge W_n^Y(\omega)$), then
$$E[M_n|\mathscr F_{n-1}] = E[W_n^X 1_{A_n}|\mathscr F_{n-1}] + 0$$
$$= E[W_n^X|\mathscr F_{n-1}] = W_{n-1}^X$$
But is it that $W_{n-1}^X = M_{n-1}$?
Not necessarily. It could be that $\omega \in A_{n-1}^C$ (ie $W_{n-1}^X(\omega) \le W_{n-1}^Y(\omega)$). Hence, $M_{n-1} = W_{n-1}^Y$
$\therefore, \because$ it is not necessarily true that $E[M_n|\mathscr F_{n-1}] = M_{n-1}$, it does not follow that $E[M_n|\mathscr F_{n-1}^M] = M_{n-1}$ QED